Orthodontic patient co-operation: a review of the clinician's role in predicting and improving patient compliance - Firth Fiona; Bennani Florence; Stacknik Suzan; Farella Mauro (Sciendo, 2019)
This systematic narrative review outlines factors associated with patient co-operation during orthodontic treatment. The co-operation of orthodontic patients, related to oral hygiene, appliance wear, diet and appointment attendance, can be highly influential on treatment outcome and the development of a number of potential adverse effects. While each patient is an individual with unique variations, patient age, gender, socio-economic status, parental relationships and psychological factors have been regarded as potential predictors of compliance. The assessment of potential patient co-operation can be difficult. A number of predictive methods have been attempted, including survey-based scales and subjective measurements, although, at present, clinicians lack a reliable quantitative tool for co-operation determination. Through communication, clinicians may alter patient co-operation. However, an individualised, patient-centred approach and the development of a relationship between the orthodontist and the patient remain essential.